The Effect of Wheat Residues and Vermicompost on the Quality Characteristics of Corn (Zea mays L.) Forage and Soil Fertility - Hasanali Pooresmaeil; Mehdi Dahmradeh; Ahmad Ghanbari (بوم شناسی کشاورزی)
IntroductionOne of the most significant agricultural challenges in arid and semi-arid regions is the decline in organic matter in agricultural soils, which leads to reduced crop yields and increased production costs. This depletion is primarily due to the annual removal of soil nutrients through crop harvesting and the extraction of organic matter. Farmers often remove straw and stubble from the field along with the grain harvest, and to prepare the field for the next planting or to control pests and diseases, they frequently burn the remaining straw. These practices contribute to a reduction in soil fertility over time. One of the most important effective factors in sustainable agriculture is plant nutrition, which uses nutrients in the soil. Sustainable production requires efficient and effective use of on-farm resources such as plant residues after harvest. The need to reduce the costs of fertilizing agricultural products by using renewable resources has revived the use of organic fertilizers worldwide. Vermicomposting is one of the promising processes for producing organic fertilizer with high nutritional value, which not only increases agricultural productivity but is also a cost-effective strategy for waste management without pollution. Materials and MethodsThe corn (Zea mays L.) variety Fajr or K.S.C 260 was used in this study. This experiment was conducted in the 2016-2017 growing season based on a randomized complete block design with three replications at the Agricultural Research Institute of Zabol University. The experimental treatments include different levels of integrated organic fertilizer management system in ten levels: no fertilization, 30% wheat residues, 60% wheat residues, 90% wheat residues, 30% vermicompost, 60% vermicompost, 100% vermicompost, 10% vermicompost+ 90% wheat residues, 40% vermicompost+ 60% wheat residues and 70% vermicompost+ 30% wheat residues. Acid detergent fiber (ADF) cell wall contribution includes cellulose and lignin, and dry matter digestibility (DMD) were measured in corn plants. Meanwhile, the amount of organic carbon, nitrogen, phosphorus, potassium, calcium, sodium, magnesium and sulfur in the soil were measured, too. Results and DiscussionAccording to the obtained results, the integrated organic fertilizer management system showed a significant effect on the organic carbon, nitrogen, phosphorus, potassium, calcium, sodium, magnesium, and Sulphate. Additionally, the integrated organic fertilizer management system showed no significant effect on the ADF and DMD of corn. The highest and lowest amount of DMD (56.35%) and ADF (16.40 g.kg-1 DM) in corn were observed due to the treatment of 60% of wheat residues and treatment of 70% vermicompost + 30% wheat residues, respectively. The highest amount of organic carbon (0.212 %) and phosphorus (5.07 mg.lit-1) were achieved in the integrated system of 10% vermicompost + 90% wheat. However, there were no significant differences statistically compared to the treatment of 70% vermicompost + 30% wheat residue. The highest and lowest percentage of soil nitrogen was observed in the integrated system of 70% vermicompost+ 30% of wheat residues (0.063%) and no fertilization (0.020%), respectively. In the present study, adding organic matter to the soil increased soil phosphorus. The mineralization and mobilization of phosphorus is due to the presence of microorganisms and enzymes that dissolve phosphorus in the intestines of earthworms. The highest amount of potassium (0.37 meq.lit-1), sulfate (11.29 meq.lit-1), and calcium (6.33 meq.lit-1) in corn were observed in the treatment of 10% vermicompost+ 90% wheat residues, 70% vermicompost + 30% wheat residues and the treatment of 30% wheat residues, respectively. ConclusionsIn general, the integrated system significantly increased the amount of organic carbon, total nitrogen, available phosphorus, available potassium, calcium, and magnesium in the soil. Organic materials increase the ability to absorb nutrients and increase the quality of corn forage by increasing DMD and reducing ADF. The results of this research demonstrated that the integrated system of 70% vermicompost and 30% wheat residue exhibited significant advantages in the characteristics under investigation, outperforming other treatments in the test area.